n the context of active ageing: volunteering and lifelong learning of older people - Fernandez, Rosario Paniagua (Miscelánea Comillas, 2014)
The world population is undergoing an aging process without precedent. This aging process is favoured by best health habits, and advancements in medicine and pharmacology, among other factors. For this reason, national and international agencies are replying with appropriate programs, so as to make sure that this stage of life is being lived in the best conditions, thereby promoting the so-called «active ageing». The aim of this work is to highlight this phenomenon, focusing on two mainideas: the contribution of the elderly to society through social volunteer work, and continuing formation as a challenge, after years of dedication to work and the upbringing and education of children.